Viden i læreruddannelsen – en typologi - Lund, Jens Hansen; Nielsen, Birgitte Lund (Studier i læreruddannelse og -profession, 2020)
Artiklen beskriver og analyserer måder hvorpå ’viden’ er konceptualiseret i diskussioner om læreruddannelse og –praksis gennem præsentation af en typologi med de fire dimensioner: videntype, håndtering af viden, viden gennem materialitet og videnindhold. Den første dimension fokuserer på, at viden kan fremstå både som global og lokal empiri og teori. Den næste dimension handler om at håndtere viden på forskellige måder, herunder tilegnelse af viden, videnbevidsthed, omsætning og produktion af viden. Den tredje dimension beskriver den materialitet, hvormed viden er ’båret’, som fx tekst eller tale. Endelig handler den sidste dimension om videnindholdet – ’hvad-spørgsmålet’, som er relevant både i en fagopdelt og transdiciplinær organisering af læreruddannelse. Potentialer og perspektiver på brug af typologien med disse fire dimensioner diskuteres og perspektiveres. The paper discusses an analytical model targeting professional discussions and refl ections about the knowledge-base in teacher education. As a starting point, examples from theoretical discussions about the knowledge-base, both historically and in contemporary research, are presented. A tendency to highlight in particular the need for research-based knowledge in a slightly reductionist way is emphasised. Continuing from this, the analytical model is presented and discussed. The model consists of four dimensions: 1) modes of k nowledge, 2) ways of handling k nowledge, 3) knowledge through materiality, and 4) knowledge in relation to content. The fi rst dimension focuses on modes in which knowledge can appear with subcategories global and local evidence, and global and local theory. The second dimension is about ways of handling knowledge including learning, consciousness about knowledge, enacting knowledge and producing knowledge. Dimension 3 covers the form in which knowledge is ‘carried’ e.g. through speech and as text. Dimension 4, know-ledge in relation to content, refers to ‘the what question’ relevant both in a subject and discipline divided approach to teacher education and in more transdisciplinary organisations. In the last part of the paper, a range of examples are discussed with use of the model.